Peran Person Job Fit pada Komitmen Karir Karyawan - Rani Rafika Duri; Tuti Rahmi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The purpose of this study was to determine the contribution of person job fit to employee career commitment. The approach used in this research is quantitative with a correlational design. The subjects who participated in this study were employees who worked at a private company in Duri City, Riau. In determining the research subjects, a saturated sampling technique was used, namely 56 people. Data were measured using a career commitment scale and a person job fit scale. Data were analyzed with the help of SPSS software version 24 for windows using a simple linear regression test. The results of the analysis showed that there was a significant contribution of 0.008 (p <0.05) between person job fit and career commitment. Based on the results of the simple regression analysis, the R square value was obtained of 0.125 which indicated that person job fit had a contribution of 12.5% ​​to employee career commitment. This finding indicates that employees with good person job fit tend to have high career commitment.